Daylighting Contribution for Energy Saving in a Historical Building. (November 2015) - Ciampi, Giovanni; Rosato, Antonio; Scorpio, Michelangelo; Sibilio, Sergio
Abstract: The purpose of this study is assessing the reliability of the software DIALux 4.12 for daylighting design, comparing experimental data with simulation results; the comparison was performed for an office. The daylight illuminance distribution inside the room, the external zenith luminance and the external horizontal diffuse illuminance were measured during the weeks from January 19 th to February 20 th ; the data gathered were further reduced to match conditions related to the CIE sky type #12 (CIE Standard Clear Sky, low luminance turbidity) and finally the comparison was carried in terms of daylight illuminance distribution and relative percentage error.